Предмет: Алгебра,
автор: qwertyuiop1329
Упростите выражение
а) -2x(1-x)+(2x-3)(x+1)
б) 4(1+3x)^2-24x
в) (x+4)(x-4)-(x-3)^2
Ответы
Автор ответа:
0
а) -2x(1-x)+(2x-3)(x+1)=-2х+2х²+2х²+2х-3х-3=4х²-3х-3
б) 4(1+3x)²-24x=4(1+6х+9х²)-24х=4+24х+36х²-24х=4+36х
в) (x+4)(x-4)-(x-3)²=х²-16-(х²-6х+9)=х²-16-х²+6х-9=-25+6х
б) 4(1+3x)²-24x=4(1+6х+9х²)-24х=4+24х+36х²-24х=4+36х
в) (x+4)(x-4)-(x-3)²=х²-16-(х²-6х+9)=х²-16-х²+6х-9=-25+6х
Похожие вопросы
Предмет: Алгебра,
автор: sahzodauciha
Предмет: Литература,
автор: angelina522518
Предмет: Русский язык,
автор: Gettin
Предмет: Литература,
автор: poplevina2004
Предмет: Литература,
автор: Аноним